Establishment of Cell Lines Derived From the Genus Macaca Through Controlled Expression of Cell Cycle Regulators. Issue 2 (February 2015) - Kuroda, Kengo; Kiyono, Tohru; Eitsuka, Takahiro; Isogai, Hiroshi; Takahashi, Koichi; Donai, Kenichiro; Isogai, Emiko; Fukuda, Tomokazu
ABSTRACT Nonhuman primates are useful animal models for the study of human diseases. However, the number of established cell lines from nonhuman primates is quite limited compared with the number established from other experimental animals. The establishment of nonhuman primate cell lines would allow drug testing on those cell lines before moving experiments into primates. In this study, we established nonhuman primate primary cell lines by introducing the genes for CDK4R24C, cyclin D1, and hTERT. These cell lines proliferated more rapidly than primary cells and bypassed cellular senescence. Karyotype analysis showed that the chromosome patterns were intact in the immortalized cell lines. Furthermore, we showed that the expression of introduced genes could be precisely controlled through the Tet‐Off system with the addition of doxycycline. The present study shows that introduction of the CDK4R24C, cyclin D1, and hTERT genes are effective methods of establishing nonhuman primate cell lines. J. Cell. Biochem. 116: 205–211, 2015. © 2014 Wiley Periodicals, Inc.